2015
DOI: 10.1121/1.4904529
|View full text |Cite
|
Sign up to set email alerts
|

Sound localization in common vampire bats: Acuity and use of the binaural time cue by a small mammal

Abstract: Passive sound-localization acuity and the ability to use binaural time and intensity cues were determined for the common vampire bat (Desmodus rotundus). The bats were tested using a conditioned suppression/avoidance procedure in which they drank defibrinated blood from a spout in the presence of sounds from their right, but stopped drinking (i.e., broke contact with the spout) whenever a sound came from their left, thereby avoiding a mild shock. The mean minimum audible angle for three bats for a 100-ms noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Bats and other small mammals have been shown to estimate azimuth with an accuracy of <10degrees (the exact accuracy depends on the azimuth, (e.g. [ 35 , 36 ])). This accuracy accounts for an inter-aural time difference of <10 μ s which is in accordance with our sampling rate (sampling at 250kHz is equivalent to an error of ~5 μ s when estimating time differences between two ears).…”
Section: Discussionmentioning
confidence: 99%
“…Bats and other small mammals have been shown to estimate azimuth with an accuracy of <10degrees (the exact accuracy depends on the azimuth, (e.g. [ 35 , 36 ])). This accuracy accounts for an inter-aural time difference of <10 μ s which is in accordance with our sampling rate (sampling at 250kHz is equivalent to an error of ~5 μ s when estimating time differences between two ears).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few animal studies have investigated sound localization to the envelopes of highfrequency sounds. There are small animals like the Jamaican fruit bat and common vampire bat, similar in size to mice, that can use the envelope ITD as a sound localization cue Heffner et al, 2015), although other species of bats could not localize an AM tone with a low-frequency carrier (Heffner et al, 2010a;Heffner et al, 2010b). In laboratory rats, sound localization performance may be enhanced by amplitude modulation (Wesolek et al, 2010).…”
Section: Itd Sensitivity In the Mousementioning
confidence: 99%
“…Previous psychophysical studies have shown that human listeners use the ITD in the envelope as a sound localization cue as well as the ITD in the fine structure (Bernstein et al, 1994;Bernstein et al, 2002;Bernstein et al, 2008;Bernstein et al, 2012;Klein-Hennig et al, 2011;McFadden et al, 1976;Nuetzel et al, 1976). Furthermore, behavioral studies suggested that some animals also localize the sound using the ITD in the envelope Heffner et al, 2015;Keating et al, 2013;Li et al, 2019). The neural basis of envelope ITD coding begins with the auditory nerve that is well-synchronized to AM sound in this range of modulation (Joris et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such ultrasonic waves are usually short in wavelength, wide in spectrum, have good time resolution, and can be used to quickly determine the direction, distance, and characteristics of the target. Bats can utilize accurate time measurement and binaural time difference for localization [17]. Figure 1 shows the echolocation signal of Bechstein’s bat ( Myotis bechsteinii ).…”
Section: Bioinspired Waveform Designmentioning
confidence: 99%